Retrospective Evaluation of Determinants of Road Traffic Injuries at a Naval Station - Agrawal, Tripti; Sinha, Sandeep Kumar; Agrawal, Nitesh (Indian Journal of Community Health, 2021)
Introduction: Several factors like globalization, industrialization, migration, access to modern ways of living, increasing income levels, easy availability of vehicles, point of use entertainment/communication gadgets, media influence and others have brought human beings in close contact with a variety of challenges to safe driving, resulting in an increased occurrence of Road Traffic injuries across the globe. Methods and Material: A cross-sectional descriptive study was conducted at naval station amongst victims of road traffic accidents who reported to emergency department of naval hospital over period of six months. Interviews on structured questionnaire to explore various determinants of road traffic injuries (RTI). Data Analysis on 156 victims was carried out for proportion of study variables of interest, Chi square test to determine significant differences between demographic variables and RTA exposure. Results: Of 156 RTA victims, more than 50% were between 21 - 40 years; 69.9% were male; 93% accidents were contributed by driving speed more than 40km/hr; 47% occurred at road junctions followed by civil roads; 27% were due to collision. 23% accidents took place on Saturdays; 36% were in morning 06 - 12 hours. 1/3 accidents were caused by two wheeler vehicles. Negligence of driver (40.4%) poor road condition (24.4%) were major causes of the accident as reported by victims. 44.2% of the victims had minor injury; 58.7% drivers who met accidents were holding valid driving license; 38% were wearing protective gears and 56% narrated that road lights/ traffic signals were available at vantage points. Exposure to accidents was found to be having statistically significant difference when related to age, gender, type of accident, common causes of accident and use of protective gears. Conclusions: The stricter application of traffic laws and safety measures are required to bring down the road traffic accident rate and related mortality.